2000
DOI: 10.1074/jbc.m000899200
|View full text |Cite
|
Sign up to set email alerts
|

Phospholemman Is a Substrate for Myotonic Dystrophy Protein Kinase

Abstract: The genetic abnormality in myotonic muscular dystrophy, multiple CTG repeats lie upstream of a gene that encodes a novel protein kinase, myotonic dystrophy protein kinase (DMPK). Phospholemman (PLM), a major membrane substrate for phosphorylation by protein kinases A and C, induces Cl currents (I Cl(PLM) ) when expressed in Xenopus oocytes. To test the idea that PLM is a substrate for DMPK, we measured in vitro phosphorylation of purified PLM by DMPK. To assess the functional effects of PLM phosphorylation we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 50 publications
0
37
0
Order By: Relevance
“…Besides CaMKII, PKC could also play a role in PLM phosphorylation in response to exercise. PLM is known to be phosphorylated by PKC (33,42,51), and several studies have indicated that PKCs are activated during exercise (23,26,43,53). The PKC superfamily is divided into three subfamilies, conventional (␣-, ␤ I -, ␤ II -, and ␥-isoforms), novel (␦-, ε-, -, and -isoforms), and atypical PKCs (-and /-isoforms), based on differences in structure and responsiveness to the second messengers, Ca 2ϩ , and diacylglycerol (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides CaMKII, PKC could also play a role in PLM phosphorylation in response to exercise. PLM is known to be phosphorylated by PKC (33,42,51), and several studies have indicated that PKCs are activated during exercise (23,26,43,53). The PKC superfamily is divided into three subfamilies, conventional (␣-, ␤ I -, ␤ II -, and ␥-isoforms), novel (␦-, ε-, -, and -isoforms), and atypical PKCs (-and /-isoforms), based on differences in structure and responsiveness to the second messengers, Ca 2ϩ , and diacylglycerol (37).…”
Section: Discussionmentioning
confidence: 99%
“…Acute exercise in rat skeletal muscle induced phosphorylation and translocation of PLM to the muscle outer membrane fraction and sarcolemmal giant vesicles, with a concomitant increase in Na ϩ -K ϩ -ATPase activity (45). Insulin and exercise are hypothesized to promote PLM phosphorylation via protein kinase A (PKA) and C (PKC) since PLM is a known substrate for both PKA and PKC (33,42,51 (4,7). PKAand PKC-mediated phosphorylation of PLM may also regulate PLM translocation to the plasma membrane of the cell (27,34).…”
mentioning
confidence: 99%
“…There was no change in the subcellular localization with either treatment (data not shown). Kinases other than PKA and PKC may act on PLM (29,37) and other FXYD family members. To determine whether phosphorylation of CHIF could affect its subcellular distribution, mutagenesis was performed on the carboxy terminus of CHIF (Table 2).…”
Section: Localization Of Plm Phosphorylation-deficient Mutant Is Not mentioning
confidence: 99%
“…NMR (10) and infrared spectroscopy (2) showed that the TM domain of PLM reconstituted in liposomes is an ␣-helix with a maximum tilt of 15-17°. Specifically, NMR spectroscopic studies of highly purified PLM in model micelles indicate that the molecule consists of four ␣-helices: H1 (residues [12][13][14][15][16][17] is in the extracellular NH 2 terminus, H2 (residues [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] is the main TM helix followed by the short H3 (residues 39 -45), and H4 (residues 60 -68) in the COOH terminus is connected to H3 by a flexible linker (36). PKA phosphorylates Ser 68 , whereas PKC phosphorylates Ser 63 and Ser 68 , of PLM (37).…”
mentioning
confidence: 99%
“…PKA phosphorylates Ser 68 , whereas PKC phosphorylates Ser 63 and Ser 68 , of PLM (37). In addition, PLM is also a substrate for myotonic dystrophy protein kinase (23) and never in mitosis A kinase (19). In transfected Madin-Darby canine kidney cells expressing mouse PLM, phosphorylation of Ser 69 is important in shifting the distribution of PLM from the endoplasmic reticulum to the plasma membrane (16).…”
mentioning
confidence: 99%